2020
DOI: 10.1088/2053-1591/ab8b89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nd2O3 and Na2O concentration on physical and spectroscopic properties of TeO2–Bi2O3–ZnO–Na2O–Nd2O3 glasses

Abstract: Two series of tellurite glasses with molar compositions of (55TeO 2 -2Bi 2 O 3 -(41-x) ZnO-2Na 2 O-xNd 2 O 3 (x=0.5, 1.0, 1.5, 2.0 and 2.5) and 55TeO 2 -2Bi 2 O 3 -(41-x) ZnO-xNa 2 O-2Nd 2 O 3 (x=1.0, 2.0, 3.0, 4.0, 5.0) were fabricated using melt quenching technique. Based on the measured densities, refractive indices and absorption spectra, physical and spectroscopic properties of these two-glass series are evaluated and compared. Whereas substitution of ZnO by Nd 2 O 3 causes the values of density and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…It was indicated that Na + not large enough to fill empty spaces inside glass network, so the consequences is the network become tenuous and the glass is lighter. Similar results also reported by [28], where substitution ZnO with Na2O decrease density due to reduction of average glass molecular weight in TBZN-Nd glasses. Opposite by density, the molar volume was increased significantly due addition of Na2O.…”
Section: Fig 1 Tzbn Glasses With Increasing Na2o Concentrationsupporting
confidence: 89%
“…It was indicated that Na + not large enough to fill empty spaces inside glass network, so the consequences is the network become tenuous and the glass is lighter. Similar results also reported by [28], where substitution ZnO with Na2O decrease density due to reduction of average glass molecular weight in TBZN-Nd glasses. Opposite by density, the molar volume was increased significantly due addition of Na2O.…”
Section: Fig 1 Tzbn Glasses With Increasing Na2o Concentrationsupporting
confidence: 89%
“…Density is a property that describes the distribution of atoms in a glass matrix. Density was measured using the pycnometer method at room temperature based on the Archimedes principle shown in Equation (1) (Marzuki et al, 2020):…”
Section: Methodsmentioning
confidence: 99%
“…Where ρg, ρw, mg, m0, m1, m2, dan m3 denote the density of glass, density of distilled water, mass of the sample, the mass of the empty pycnometer, the mass of pycnometer with the sample inside, the mass of the pycnometer filled with water and glass sample, and mass of the pycnometer filled with water. The relationship between density and molar volume is expressed in the following equation (Marzuki et al, 2020)…”
Section: Methodsmentioning
confidence: 99%
“…When considering molecular weights, it is evident that B2O3 exhibits a significantly lower value than ZnO (69.63 g/mol: 81.38 g/mol). Moreover, this trend is mirrored in the atomic masses, with B showing a substantially lighter value compared to Zn (10.81 amu: 65.38 amu) which increases the total glass molecular weight [37] [38]. Besides that, the introduction of Zn 2+ ions disrupts the Te-O chain, leading to a modification in the glass structure [33], that is by expanding bridging oxygen's (BO) linkage [39].…”
Section: Calculated Densitymentioning
confidence: 99%